ANALISIS TERHADAP KEDUDUKAN PIUTANG PAJAK SEBAGAI KREDITOR PREFEREN BERHADAPAN DENGAN KREDITOR SEPARATIS DALAM PEMBAYARAN UTANG HARTA PAILIT (STUDI PUTUSAN PENGADILAN NIAGA NOMOR: 57/PDT.SUS-RENVOI PROSEDUR/2011/PN.NIAGA. JKT.PST) - DANIEL CENDRICO (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Sunarmi2. Dedi Harianto3. T. Keizerina Devi A A curator plays an important role in distributing bankruptcy property, but it is not uncommon that there is incompatibility in the distribution between its amount and the curator’s demand. The result of the research showed that the organization and the settling of bankruptcy property related to the position of tax creditor, the preferred creditor should be prioritized and the remaining payment is then paid to the secured creditor. Viewed from its utility, the verdict has given the benefit in dunning the tax payable in the post-debtor’s bankruptcy. Even though not the whole tax payable can be billed, at least the court’s verdict has given legal certainty to the litigants.Keywords: Preferred Creditor, Secured Creditor, Tax Payable